The Effectiveness of the Procurement at the Construction Services Selection Implementation Center - . Sofian; H. Parung; S. Burhanuddin; R. Arifuddin (Civil Engineering Journal, 2024)
The construction industry still faces various challenges in some developing countries, and one of the problems is the procurement of goods and services. The allocation of public procurement funds is significant to the national GDP. It is essential to conduct comprehensive research on government procurement in the construction industry in Indonesia due to the rapid growth of the construction industry in the last decade. This research focuses on the procurement of construction goods and services in the Ministry of Public Works and Housing by looking at the perception of the government as the project owner. This research aims to identify a model of critical success factors to improve public procurement performance in the construction industry from the government's perspective. The research method includes two stages, namely, the development of critical success, which consists of crucial factors and indicators that affect the performance of public procurement in the construction industry. It is a literature study of relevant previous research results from various countries that affect these critical success factors. Then, the second stage is a survey of experts' perceptions through questionnaires. The questionnaire data analysis used SEM-PLS software to quantify the relationship model of critical success factors to improve the performance of government procurement of goods and services in the construction industry. Data processing results include: business process factors affect 97.1%, regulatory factors affect 90.1%, information system factors affect 63.1%, human resource factors affect 56.1%, organizational factors affect 46.1%, and monitoring and evaluation factors affect 38%. Doi: 10.28991/CEJ-2024-010-03-013 Full Text: PDF